Electrical and optical characterization of extended defects induced in p-type Si after Si ion implantation - Cloud Nyamhere (Wiley, 2022)
In this work we present the analysis of small interstitial clusters (ICs) introduced in p-type Si after ion implantation using deep level transient spectroscopy (DLTS) and photoluminescence. Silicon ions with energy 380 keV and fluence of 1.0 x 1012 cm-2 have been implanted into bulk p-type Si and post-implant annealing at temperatures between 500 oC and 800 oC specifically to create small interstitial cluster (ICs) defects. In the samples annealed at 500 oC, DLTS spectra show deep level hole traps at EV + 0.20 eV, EV + 0.25 eV, EV + 0.36 eV, and EV + 0.50 eV. The hole traps EV + 0.36 eV and EV + 0.50 eV have been attributed to the small Si self-interstitial clusters. After increasing the post-implant anneals to 600 oC there is a significant decrease in defect concentration and all the defects are annealed-out at 700 oC. Photoluminescence (PL) spectroscopy of the samples reveals optical band levels, at 1218 nm (1.019 eV), and 1233 nm (1.007 eV) which have both been attributed to interstitial cluster defects. The interstitial cluster-related optical band levels have been observed in the samples annealed at 500 oC which correlate well with DLTS measurements. (© 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim)